2022
DOI: 10.3390/app12125839
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Use of Fucoxanthin and Phycobiliproteins into Solid Matrices to Increase Their Emission Quantum Yield and Photostability

Abstract: In the search for a better and brighter future, the use of natural luminescent renewable materials as substitutes for synthetic ones in the energy field is of prime importance. The incorporation of natural pigments (e.g., xanthophylls and phycobiliproteins) is a fundamental step in a broad spectrum of applications that are presently marred by their limited stability. The incorporation of bio-based luminescent molecules into solid matrices allows the fabrication of thin films, which may dramatically increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…To improve the processability of the phycobiliproteins, the PC molecules were entrapped into solid matrices, such as poly (vinyl alcohol (PVA) ( Dias et al, 2022 ). It was demonstrated that the ability to down-shift the UV radiation observed for the biomolecules in solution ( Figure 2 ) was kept after their incorporation into the host, Figure 3 .…”
Section: Phycobiliproteins Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…To improve the processability of the phycobiliproteins, the PC molecules were entrapped into solid matrices, such as poly (vinyl alcohol (PVA) ( Dias et al, 2022 ). It was demonstrated that the ability to down-shift the UV radiation observed for the biomolecules in solution ( Figure 2 ) was kept after their incorporation into the host, Figure 3 .…”
Section: Phycobiliproteins Applicationsmentioning
confidence: 99%
“… (A) Photographs of PC incorporated in PVA ( Dias et al, 2022 ) under white light (top) and UV irradiation at 365 nm (bottom). Scale bars: 10 –2 m. (B) Emission and excitation spectra excited at 575 nm and monitored at 720, respectively.…”
Section: Phycobiliproteins Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pigment is the main phycobiliprotein found in red seaweed (Rhodophyta) [15], such as Euchema sp, Gelidium sp [16], Gelidium amansii [17], Gelidum elegans [13], Gelidium pusillum [18], Gracilaria sp. [5], Gracilaria changii [19], Gracilaria gracilis [20,21], Halymenia sp. [16], Halymenia durvillaei [22], Pyropia haitanensis [23], etc.…”
Section: Biopigments (Pe Fx and Sx) From Seaweedsmentioning
confidence: 99%